DEKOMPOSISI BERBAGAI JENIS SERESAH GAMAL DI HUTAN PENDIDIKAN WANAGAMA 1, GUNUNG KIDUL, YOGYAKARTA - Nurjanto, Handojo H.; Supriyo, Haryono; Widyastuti, Siti M.; Kabirun, Siti (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2016)
Plant litter is the major source of organic matter in the forest floor and litter decomposition plays an important role in the organic matter and nutrient entry to the soil. The decomposition rate is strongly influenced by climatic conditions and initial chemical composition of the litter. Litter in the rehabilitated forest area of Wanagama 1 Education Forest is dominated by Gamal (Gliricidia sepium) litter which isconsisted of leaves, twigs and fruit pods. This study assessedthe decomposition rate of leaf, twig and fruit podlitter of Gamal in compartment 5 and 6 of Wanagama 1 Education Forest. To assess effect of season, the research was conducted in dry season (August to November 2012) and in rainy season (from January to March 2013). The results showed that the decomposition rates of leaf, twig and fruit pod litter of Gamal in dry season were moderate with k (decomposition index) = 0.0074 – 0.0065, slow (k = 0.0043 – 0.0040), andslow (k = 0.0031 – 0.0026), respectively.In the rainy season, the decomposition process was faster with decomposition rates were high (k = 0.0132 – 0.0161), moderate (k = 0.0073 – 0.0065) and moderate (k = 0.0055 – 0.0063), respectively. There was no effect of compartments which differed in the stand density. Keywords : Decomposition Rate, Kind of Litter, Gamal (Gliricidia sepium), Season